AKIBAT HUKUM TIDAK ADANYA PENGATURAN PENGAWASAN DAN EVALUASI PENATAAN RUANG SEBAGAI BAGIAN DARI INSTRUMEN PRINSIP KEHATI-HATIAN DALAM PERDA RTRW PROVINSI MALUKU - Laode Angga (Universitas Janabadra, 2016)
The legal effects of the lack of monitoring and evaluation regulation of spatial planning as a part of the instrument of precautionary principle in the local regulation on spatial plans of Maluku Province is contrary to Article 55-59 of the Law No. 26 of 2007 on Spatial Planning and Article 44 No. 32 of 3009 on Environmental Protection and Management. Based on the principles of the legislation forming, The lack of monitoring and evaluation of spatial planning as part of the precautionary principle instrument in the local regulation of Maluku Province No. 16 of 2013 on Spatial Plans of Maluku province is contrary to one of the legislation principles, namely: The higher legislation rules out the lower legislation. If there is a contradiction between higher legislation level and lower legislation level, the higher legislation is enforced and lower legislation is ruled out.Therefore the local regulation of Maluku Province No. 16 of 2013-2033 on the Spatial Plans of Maluku province that has not been set up monitoring and evaluation of spatial planning as a part of the instrument of the precautionary principle should be revisited for revision.